Dialects - Trudgill, Peter (Routledge, 2004)
Dialects introduces the many dialects of English spoken in the United Kingdom and reveals the key issues that dialectology engages with.- Resumé vydavatel
Keywords: angličtina -- Velká Británie; dialekty -- Velká Británie; English language -- Great Britain; dialects -- Great Britain; elektronické knihy; pracovní sešity; electronic books; activity books